Design of an UHPC with local materials: procedures, properties and modelling parameters - Santos Junior, Gilvan Bezerra dos (2023)
Ultra-high performance concrete (UHPC) is a cementitious composite with high compressive and tensile strength and ductile behavior. Its mixture comprises Portland cement, silica fume (SF), a filler, fine sand, superplasticizer admixture, a low water-to-binder ratio, and a high steel microfiber volume. Although UHPC production is now disseminated worldwide, its manufacturing and property evaluation are complex. Hence, a correct selection of materials and equipment is necessary. This thesis focuses on developing and evaluating a UHPC mixture with local materials and available regular laboratory equipment. Initially, in selecting materials, each local raw material's mineralogical and chemical compositions and particle size were determined for an accurate choice. The mixing procedure was tested in a three-speed horizontal pan mixer with different stages to obtain a homogeneous and self-compacting mixture. The design method utilized was the Modified Andreasen and Andersen. After determining the initial composed mix curve, some adjustments refined the mix design to obtain the required properties. To validate the UHPC developed, the physical and mechanical properties were evaluated. The tests were performed according to the Brazilian Standards and the French NF P18-470. The compression test was carried out with low load rates to obtain the post-peak descending branch. The tensile curve was determined indirectly through an inverse analysis by 3-point and 4-point bending tests. In addition, the splitting test response was evaluated. Lastly, the mechanical tests were utilized to obtain the parameters needed to define the material in a finite element numerical analysis. This work confirms that producing UHPC with local materials and regular laboratory equipment is possible. Starting from the correct selection of materials and procedures, 130 MPa compressive and 6.5 MPa elastic tensile 28-day strengths were achieved with a practically self-compacting material and superior durability parameters of 1.02% air content and 3.0% water porosity. The step-by-step inverse analysis response was compared to simplified methods, and the French Standard Institute (AFNOR) and Japan Society of Civil Engineers (JSCE) standardized tensile curves presented a better fit. Furthermore, the Concrete Damage Plasticity (CDP) model parameters were obtained and calibrated according to compression and flexural responses.